Interaction between cigarette smoking and genetic polymorphisms on the associations with age of natural menopause and reproductive lifespan: the Singapore Chinese Health Study. Issue 6 (12th April 2022) - Huang, Zhongwei; Chang, Xuling; Wang, Ling; Liu, Jianjun; Heng, Chew-Kiat; Khor, Chiea-Chuen; Yuan, Jian-Min; Koh, Woon-Puay; Dorajoo, Rajkumar
Abstract: STUDY QUESTION: Are there genetic variants that interact with smoking to reduce reproductive lifespan in East-Asian women? SUMMARY ANSWER: Our study corroborates several recently identified genetic loci associated with reproductive lifespan and highlights specific genetic predispositions that may interact with smoking status to adversely affect reproductive lifespan in East-Asian women. WHAT IS KNOWN ALREADY: Epidemiological data as well as evaluations on genetic predisposition to smoke indicate on the importance of smoking in adverse effects on reproductive lifespan in women. However, there are no previous smoking and gene interaction studies for reproductive traits in East-Asian women. STUDY DESIGN, SIZE, DURATION: This population-based prospective cohort study comprised 11 643 East-Asian Chinese women with overlapping genome-wide genotyping and reproductive data. PARTICIPANTS/MATERIALS, SETTING, METHODS: We performed a genome-wide association study for reproductive lifespan in women (n = 11 643) from the Singapore Chinese Health Study (SCHS) and carried out a genome-wide interaction study to identify loci that interacted with smoking status to affect age of natural menopause and reproductive-time. MAIN RESULTS AND THE ROLE OF CHANCE: Two known loci associated with menopause, rs113430717 (near HMCES, chromosome 3, P meta = 5.72 × 10 −15 ) and rs3020136 (near RAD21, chromosome 8, P meta = 1.38 × 10 −8 ) were observed beyond genome-wide levels of association with age at menopause in this study. For reproductive lifespan, the genome-wide association observed at rs79784106 (chromosome 3, P meta = 5.05 × 10 −12 ) was in linkage disequilibrium with the menopause lead single-nucleotide polymorphism (SNP) (rs113430717). Four additional loci, first reported to be associated with menopause, were also associated with reproductive lifespan in our study ( P Adj between 7.42 × 10 −5 to 4.51 × 10 −3 ). A significant interaction was observed between smoking and an East-Asian specific SNP, rs140146885, for reduced reproductive lifespan, per copy of the minor C allele (beta = −1.417 years, P interaction = 2.31 × 10 −10 ). This interaction was successfully replicated in additional independent samples (beta = −1.389 years, P interaction = 6.78 × 10 −3 ). Another known variant associated with menopause, rs11031006 (near FSHB ), was also observed to interact with smoking status to reduce age at menopause in our dataset (beta = −0.450 years, P adj = 0.042). LIMITATIONS, REASONS FOR CAUTION: The modest sample size of the replication datasets used likely affected the statistical power to firmly replicate all identified novel loci observed in our smoking interaction analyses. WIDER IMPLICATIONS OF THE FINDINGS: Age of natural menopause and reproductive lifespan have clear genetic predispositions with distinct ethnic differences, and they may be adversely truncated by lifestyle factors such as smoking, which can pose a significant impact on the reproductive lifespan and future health outcomes in women. STUDY FUNDING/COMPETING INTEREST(S): The Singapore Chinese Health Study is funded by the National Medical Research Council, Singapore (NMRC/CIRG/1456/2016), National Institutes of Health (R01 CA144034 and UM1 CA182876) and National Research Foundation, Singapore (Project Number 370062002). W.-P.K. is supported by the National Medical Research Council, Singapore (MOH-CSASI19nov-0001). The corresponding author had full access to all the data in the study and had final responsibility for the decision to submit for publication. The authors do not report conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.